Spinal meningiomas, from biology to management - A literature review - Serratrice, Nicolas; Lameche, Imène; Attieh, Christian; Chalah, Moussa A; Faddoul, Joe; Tarabay, Bilal; Bou-Nassif, Rabih; Ali, Youssef; Mattar, Joseph G; Nataf, François; Ayache, Samar S; Abi Lahoud, Georges N (Frontiers in Oncology, 2023)
Meningiomas arise from arachnoidal cap cells of the meninges, constitute the most common type of central nervous system tumors, and are considered benign tumors in most cases. Their incidence increases with age, and they mainly affect females. Spinal meningiomas account for 25 to 46% of primary spinal tumors. Spinal meningiomas could be detected incidentally or be unraveled by various neurological symptoms, such as back pain, sensorimotor deficit, and sphincter dysfunction. Magnetic resonance imaging (MRI) is the preferred diagnostic modality for spinal meningiomas and permits their classification into four categories based on their radiological appearance. According to the World Health Organization (WHO) classification, most spinal meningiomas (80%) are grade I, which have benign histology and indolent behavior. In 20% of cases, they are of higher grade (grade II and III) with atypical to malignant histology and a more aggressive course. To date, surgery is the mainstay of treatment, and 70-80% of meningiomas can be cured by surgical resection. Advances in surgical techniques (microsurgery, ultrasonic dissection, intraoperative monitoring) increase the complete resection rate. The prognosis of surgically treated patients is satisfactory, even when the preoperative neurological status is poor. Adjuvant therapy has a growing role in treating spinal meningiomas, mainly in the case of a subtotal resection and tumor recurrence. The current paper reviews the fundamental epidemiological and clinical aspects of spinal meningiomas, their histological and genetic characteristics, and their management, including the various surgical novelties and techniques.